Difficulty Remembering and Writing Hijaiyyah Letters In Ealry Childhood - Sumarni, Sri; Chantika, Bunga; Oktariani, Selvia; Pagarwati, Lia Dwi Ayu (JURNAL PENDIDIKAN USIA DINI, 2026)
Literacy begins to be applied from the early childhood level to help children understand the world and express thoughts orally and in writing. Literacy is also applied in extracurricular activities, such as IMTAQ literacy which deals with the Qur'an and Arabic symbols, including Hijaiyah letters. However, early childhood often has difficulty in remembering and writing Hijaiyah letters because they are similar to each other. This difficulty is also influenced by the concentration factor, because early childhood is not yet able to focus fully on learning activities. This study aims to describe the difficulties faced by children at TK Negeri Pembina Pemulutan Barat and identify the causes of difficulties in reading and writing Hijaiyah letters. The method used is descriptive qualitative through interviews and observations. The results showed that 25% of children experienced difficulties, due to the low intensity of habituation, traditional teaching methods, and less attractive learning media. For this reason, innovative approaches, methods and media are needed so that the ability to remember and write Hijaiyah letters in early childhood can be improved.